Brain-gut-liver axis: Chronic psychological stress promotes liver injury and fibrosis via gut in rats - Xu, Meng-Yang; Guo, Can-Can; Li, Meng-Ying; Lou, Yu-Han; Chen, Zhuo-Ran; Liu, Bo-Wei; Lan, Ling (Frontiers in Cellular and Infection Microbiology, 2022)
Background The effect of chronic psychological stress on hepatitis and liver fibrosis is concerned. However, its mechanism remains unclear. We investigated the effect and mechanism of chronic psychological stress in promoting liver injury and fibrosis through gut. Methods Sixty male SD rats were randomly assigned to 6 groups. Rat models of chronic psychological stress (4 weeks) and liver fibrosis (8 weeks) were established. The diversity of gut microbiota in intestinal feces, permeability of intestinal mucosa, pathologies of intestinal and liver tissues, collagen fibers, protein expressions of toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), nuclear factor kappa β (NF-κβ), tumor necrosis factor α (TNF-α) and interleukin 1 (IL-1) in liver tissue, liver function and coagulation function in blood and lipopolysaccharide (LPS) in portal vein blood were detected and analyzed. Results The diversities and abundances of gut microbiota were significant differences in rats among each group. The pathological lesions of intestinal and liver tissues, decreased expression of occludin protein in intestinal mucosa, deposition of collagen fibers and increased protein expression of TLR4, MyD88, NF-κβ, TNF-α and IL-1 in liver tissue, increased LPS level in portal vein blood, and abnormalities of liver function and coagulation function, were observed in rats exposed to chronic psychological stress or liver fibrosis. There were significant differences with normal rats. When the dual intervention factors of chronic psychological stress and liver fibrosis were superimposed, the above indicators were further aggravated. Conclusion Chronic psychological stress promotes liver injury and fibrosis, depending on changes in the diversity of gut microbiota and increased intestinal permeability caused by psychological stress, LPS that enters liver and acts on TLR4, and active LPS-TLR4 pathway depend on MyD88. It demonstrates the possibility of existence of brain-gut-liver axis.